Hubungan Komunikasi Interpersonal dan Pola Asuh Orang Tua dengan Kenakalan Remaja di SMPN 3 Banawa - Masyita; Sringati; Arniawan (KEWINUS: Jurnal Keperawatan dan Kesehatan, 2025)
Adolescence is a transitional period marked by emotional instability and a tendency toward impulsive behavior. Inadequate parental interpersonal communication and inappropriate parenting styles are considered contributing factors to juvenile delinquency. This study aimed to analyze the relationship between parental interpersonal communication and parenting styles with juvenile delinquency among students at SMPN 3 Banawa. A quantitative study with a crosssectional design was conducted. The population consisted of 114 eighth-grade students, with 53 respondents selected using proportional stratified random sampling. Data were collected using questionnaires and analyzed using the chi-square test. Most respondents had moderate parental interpersonal communication (37.7%), democratic parenting styles (50.9%), and moderate levels of juvenile delinquency (56.6%). Statistical analysis showed a significant relationship between parental interpersonal communication and juvenile delinquency (p = 0.006), as well as between parenting styles and juvenile delinquency (p = 0.000). There is a significant relationship between parental interpersonal communication and parenting styles with juvenile delinquency among students at SMPN 3 Banawa.